Rethinking marketplace culture: Play and the context of context. (December 2019) - O'Sullivan, Stephen R.; Shankar, Avi
Play theory has been underutilized to understand consumer behaviour. In this article, we adopt a play theory perspective to understand how consumers respond to and navigate macrostructural influences. The marketplace culture stream of consumer culture theory (CCT) research is particularly well suited to macrostructural analysis from a play theory perspective. We develop an analytical framework derived from play theory to interpret the context of marketplace culture. We show how the types of play foundational to marketplace culture experiences act as expressions of order or disorder to wider macrostructural influences. In contrast to agentic perspectives, we show how marketplace culture experiences, despite their fun appearance, embody the underlying tensions of the intensifying rationality, regulation and competition structuring neoliberal society. Finally, we express concern over the marketer's control of playground expression and suggest CCT adopt a more critical stance to the commercialization of play.